Evaluation of the Influence of Process Parameters on the Properties of Resveratrol-Loaded NLC Using 22 Full Factorial Design - Shimojo, Andréa (2019)
Resveratrol (RSV) is a natural antioxidant commonly found in grapes, berries, and nuts that has shown promising results in the treatment of a variety of degenerative and age-related diseases. Despite the proven beneficial results on reduction of reactive oxidant species (ROS) and on inflammatory process, RSV shows various limitations including low long-term stability, aqueous solubility, and bioavailability, restricting its applications in the medical-pharmaceutical area. To overcome these limitations, it has been applied in pharmaceutical formulations as nanostructured lipid carriers (NLC). Thus, the present study focuses on the optimization of the production process of NLC. NLC was produced by high shear homogenization (HSH) and ultrasound method (US) using Compritol® ATO C888 as solid lipid and Miglyol 812® as liquid lipid. In order to obtain an optimized formulation, we used a 22 full factorial design with triplicate of central point investigating the effects of the production process parameters; shear intensity and homogenization time, on the mean particle size (PS) and polydispersity index (PDI). Instability index, encapsulation efficiency, and production yield were also evaluated. As the PS and PDI values obtained with 6 min of shear at 19,000 rpm and 10 min of shear and 24,000 rpm were similar, the instability index (<0.1) was also used to select the optimal parameters. Based on the results of the experimental design and instability index, it was concluded that the shear rate of 19,000 rpm and the shear time of 6 min are the optimal parameters for RSV-loaded NLC production. Factorial design contributed therefore to optimize the variables of the NLC production process from a small number of experiments.